An evaluation study on the cumulative impact damages of reinforced concrete piers based on modal frequencies. (January 2021) - Zhou, Xiwu; Zhou, Ming; Gao, Yushen; Zhang, Guoxue
Highlights: Horizontal impact test is conducted on scaled RC bridge piers by using drop hammer test system. Modal frequencies of structure decrease gradually with the damage degree development. Reliable method for evaluating impact damage based on modal frequencies is proposed and validated. Abstract: In this study, in order to accurately evaluate the cumulative impact damages undergone by concrete piers, lateral impact testing of reinforced concrete piers was carried out using an ultra-high drop hammer test system to impose damages. Then, modal frequency tests of the impacted piers were conducted one by one. It was found that, according to such parameters as the reinforcement stress and strain levels, crack widths, column top displacements, and so on, which had been obtained from experimental results, and based on the existing research results and codes, the evaluation criteria of the cumulative impact damages of reinforced concrete piers based on modal frequencies could be proposed for the bending failure components. In addition, it was confirmed that when the aforementioned evaluation criteria was adopted, timely nondestructive testing could be effectively conducted for damaged piers, and the status of the piers could be quickly determined in order to ensure the safety of passing vehicles.